Evaluation of Subchronic Toxicity of Costus speciosus Rhizome Through Changes in Renal Function in White Rats - Aulia Nurfazri Istiqomah; Ogi Dienda Pratama; Agus Sulaeman (PT CENDEKIA SCIENCE AND TECHNOLOGY, 2025)
Costus speciosus (commonly known as pacing rhizome) has been traditionally used for various therapeutic purposes, yet data on its long-term safety, particularly regarding renal function, remain limited. This study aimed to evaluate the subchronic toxicity of C. speciosus rhizome extract through renal function assessment in white Wistar rats, addressing a critical gap in preclinical safety evidence and supporting the development of standardized herbal preparations. Forty healthy Wistar rats, equally divided by sex, were acclimatized for seven days and randomly assigned to control and treatment groups. The treatment group received C. speciosus rhizome extract orally at a dose of 300 mg/kg body weight daily for 90 days, while the control group received a vehicle solution (Na-CMC). Body weight was monitored regularly, and at baseline (T0) and at the end of the study (T90), blood samples were collected for biochemical analysis of serum creatinine and urea levels. Additionally, kidney organ indices were determined, and histopathological examinations were performed to detect potential structural changes. The results indicated that body weight gain in both male and female rats was comparable between control and treatment groups throughout the study, with no statistically significant differences. Serum creatinine and urea levels remained within normal physiological ranges at both T0 and T90, and no significant differences were observed between groups. Kidney organ indices showed minor variations that were not statistically significant, and histopathological evaluation revealed no treatment-related abnormalities. In conclusion, subchronic oral administration of C. speciosus rhizome extract at 300 mg/kg body weight for 90 days did not produce nephrotoxic effects in Wistar rats. The extract was well tolerated, and renal function remained intact, supporting its safety profile. These findings provide foundational evidence for the safe development of C. speciosus as a standardized herbal medicinal product, addressing the urgent need for scientifically validated data on its long-term safety.